إحياء اللغة العربية؛ من الوعي بالتراث إلى الرؤية المستقبلية - Ahmadi Usman Sirathan (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2014)
This article tries to present the issues shown by Bintu as-Syathi’, which is related to language as it relates to the Arab community in the contemporary life. One of these issues; the issue of literary discourse and new values that can reveal by reading Arabic literature, and the issue of reviving the Arab heritage and its advantages in contemporary life, and the issue of language and nationalism and its strong relationship among those, and the issue of the Paschal and slang in the floklore, that which one is better to practice for Arabic leterary. All of those issues are important which must be attended by every one who want to revive the Arabic language. This revival in the Bintu as-Syathi’ opinion must start from an awareness of the heritage as a basis for starting to the future of Arabic language.